2021
DOI: 10.3390/f12101420
|View full text |Cite
|
Sign up to set email alerts
|

Color Change and Physical-Mechanical Properties of Polystyrene-Impregnated Glulam from Three Tropical Fast-Growing Wood Species

Abstract: The aims of this work were to determine the color change and physical–mechanical properties of polystyrene glulam from three tropical wood species. Wood laminas were cut from logs harvested from a young plantation forest of manii (Maesopsis eminii), mangium (Acacia mangium), and rubber-wood (Hevea brasiliensis). The laminas were impregnated with monomer styrene that was polymerized using potassium peroxy-disulfate as a catalyst and heat. Three-layer glulam was constructed from the polystyrene laminas, using is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Referring to Hadi et al [ 23 ], after a one-year exposure in the field, four Polish woods with polymer loading between 88 and 135% had a weight loss of 19%, while the untreated woods had 100% weight loss or totally failed. Nevertheless, the polystyrene weight gain of laminae should be considered to a certain degree, along with its optimal mechanical properties, as mentioned by Hadi et al [ 17 ], who noted that the shear strength and rupture modulus of polystyrene glulam were lower than those of solid wood.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Referring to Hadi et al [ 23 ], after a one-year exposure in the field, four Polish woods with polymer loading between 88 and 135% had a weight loss of 19%, while the untreated woods had 100% weight loss or totally failed. Nevertheless, the polystyrene weight gain of laminae should be considered to a certain degree, along with its optimal mechanical properties, as mentioned by Hadi et al [ 17 ], who noted that the shear strength and rupture modulus of polystyrene glulam were lower than those of solid wood.…”
Section: Resultsmentioning
confidence: 99%
“…The laminae were placed with a longitudinal fiber orientation along the length of the glulam. Isocyanate glue was applied with a single spread glue line at 280 g/m 2 [ 17 ], and the laminae were then cold-pressed with a specific pressure of 10 kg/cm 2 for 3 h, followed by conditioning at room temperature for two weeks in the laboratory of the Centre for Standardization of Sustainable Forest Management Instruments, Ministry of Environment and Forestry, Bogor, Indonesia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has good dimensional stability, hardness, strength, and abrasion resistance, making it widely used in the fields of construction, furniture, musical instruments, and industrial equipment [ 7 ]. For instance, previous studies have utilized various monomers, including styrene [ 8 ], methyl methacrylate [ 9 ], n-butyl acrylate [ 10 ], alkoxysilane coupling agents [ 11 ], vinyl monomers [ 12 ], methyl methacrylate (MMA) [ 13 ], and unsaturated polyester resins [ 14 ], to impregnate the wood and polymerize, filling the cell lumina to enhance the strength and dimensional stability of the wood. Research has shown that the composite treatment of wood with functional monomers, such as propylene oxide and methyl methacrylate monomers [ 15 ], ethylene/methyl methacrylate, and styrene/acrylonitrile monomers [ 16 ], can improve the comprehensive performance of wood.…”
Section: Introductionmentioning
confidence: 99%